Mitochondrial DNA and Population Genomics Reveal Additional Cryptic Diversity in the Green Salamander (Subgenus Castaneides) Species Complex - Niemiller, Matthew L.; Davis, Mark A.; Tan, Milton; Apodaca, J. J.; Dooley, Katherine E.; Cucalón, Roberto V.; Benito, Joseph B.; Niemiller, K. Denise Kendall; Hardman, Rebecca H.; Istvanko, Daniel; Thames, Dustin (Frontiers in Conservation Science, 2022)
Cryptic species present particular challenges to biodiversity conservation, as true diversity and distributional boundaries remain obscured. However, modern molecular tools have afforded unparalleled opportunities to elucidate cryptic species, define their distributions, and, ultimately, develop conservation interventions to extend their evolutionary trajectories into the future. The Green Salamander (Aneides aeneus) complex provides an evolutionary focal point and the Appalachian Highlands an ecological context for the exploration of cryptic speciation in an imperiled taxon. A recent study uncovered significant levels of genetic and genomic variation geographically structured across the Appalachian Highlands, including up to four lineages, one of which (A. caryaensis) was described therein. Here we extend the genetic and genomic examination of the Castaneides species complex by intensive sampling of additional populations along Cumberland Plateau and Appalachian Valley and Ridge of Alabama and Tennessee, employing both mtDNA and RADseq species delimitation approaches to delineate cryptic diversity and boundaries in this region. Analyses of two mitochondrial loci (nd4 and cytb) identified two reciprocally monophyletic lineages, which are also supported by population clustering and phylogenetic analyses of SNPs, that identified two population clusters with no evidence of gene flow. Our genetic and genomic results support the recognition of two additional cryptic lineages in the Castaneides species complex. Ultimately, this information is critical in developing successful adaptive management strategies for this important and endemic component of Appalachian Highland biodiversity.